Exploration of Machine Learning Techniques over Weather Forecasting - et al., Ms. Gayathiri Kathiresan (International Journal of Advanced Science and Technology, 2020)
Climatic conditions play a vital role in the production by many of our primary sectors. Nowadays we could experience a drastic change in the climates often. Based on the current scenarios the old traditional way of predicting the weather has become less accurate and hence we are forced to overcome such situations by proposing improved, innovative, and effective machine learning algorithms to predict the weather. Ineffective predictions could affect a nation’s economy like when we see a decrease in the production of farming sector and the lives of people could get threatened by natural calamities even. In the process of overcoming the problem of ineffective weather prediction there were several algorithms being proposed. In this paper, we will analyze the effectiveness of some of the proposed methods on predicting the weather conditions. Recall, F-Measure and MCC were decided to be the parameters for this comparison.